Two-dimensional materials saturable absorber for generation of ultrashort pulse fiber lasers / Anas Abdul Latiff - Anas, Abdul Latiff (2018)
Two-dimensional (2D) material likes graphene, topology insulators (TIs), transition metal dichalcogenides (TMDs), Black Phosphorus (BP) and transition metal oxides (TMOs) have recently emerged as a promising solution for generating ultrashort pulse fiber lasers. These lasers have a high market potential for laser sensing and spectroscopy, material processing, and also medical applications since it has more compact in geometry and simpler in setup. Sharing some advantages from fiber technology, the developed laser is more robust, zero-alignment, and less operational cost. This study aims to develop ultrashort pulse fiber lasers operating at 1-, 1.55-, and 2-micron regions using new 2D materials as a saturable absorber (SA). Three new materials; MoS2, BP, and TiO2 are explored in this thesis. These SAs are fabricated and characterized in term of nonlinear absorption parameters. Furthermore, field emission scanning electron microscope (FESEM), electron dispersion spectroscopy (EDS), and Raman spectroscopy are being performed to confirm the presence of 2D materials in the fabricated SA. To validate the fabricated SA’s performance, the SA is integrated into the laser cavity by sandwiching a piece of SA in between two fiber ferrules. The ultrashort pulsed fiber lasers are based on all-fiber ring cavity configuration utilizing Ytterbium doped fiber (YDF), Erbium doped fiber (EDF), Thulium doped fiber (TDF), and Thulium-Holmium co-doped fiber (THDF) as a gain medium as well as to provide a sufficient nonlinearity in the cavity. To avoid a self-pulsing instability, the free-polarization isolator is used to suppress a Brillouin backscattering. This can guarantee the pulse generation from the fiber laser owes from the SA. In some condition, additional nonlinear fiber is required to induce sufficient nonlinear effects in the cavity. Dispersion is one of another important cavity parameters where a large anomalous dispersion is normally preferable in the cavity to produce short pulse width and higher peak power. Ultrashort pulse fiber lasers operating at 1-, 1.55-, and 2-micron regions with various performances are successfully achieved in this work. For instance, MoS2 based mode-locked EDF laser produces a stable pulse train at 4 MHz repetition rate with 1.71 ps pulse width and the maximum pulse energy of 1.66 nJ is obtained at 250 mW pump power. These findings show that 2D nanomaterials have a great potential for photonic applications.